Drying performance of inclined bed dryer with air flow reversal and its effects on rice milling quality - Ghiasi, Maryam (2016)
Drying rice grains to a safe moisture content is always a critical issue in humid tropical countries such as Malaysia. Observations show that conventional drying with flat and inclined-bed dryers are the most common drying practices in Malaysian rice processing industry. Many studies evidently proved that due to inappropriate set of drying conditions and also profound moisture and temperature gradients inside grain bed, these dryers produce rice with relatively low and also non-uniform milling quality. Besides, less satisfactory drying efficiency associated with energy consumption and drying capacity were observed for these popular fixed-bed dryers. Thus the first main objective of this study was to investigate on optimum drying condition for rice drying with flat and inclined bed dryers in order to ensure maximum drying efficiency and rice milling quality. In addition, single and periodic air flow reversal techniques in conjunction with one stage and two stage drying were introduced in order to improve rice drying performance. To carry out this study, laboratory flat-bed and inclined-bed dryers were designed and fabricated based on industrial dryer conditions. Drying experiments were carried out with different variations of air flow reversal, bed depth and temperature. Consequently, the effects of all drying experiments on drying performance, drying capacity, energy usage, and rice milling quality were evaluated. Results revealed that although both dryers produced rice within acceptable milling quality range but inclinedbed dryer showed significantly better performance in terms of throughput capacity and energy consumption compared to flat-bed dryer for all applied temperatures. Furthermore, comparative analysis results between conventional and one stage air flow reversal drying showed that changing the direction of air flow during drying operation had phenomenal effects on rice milling quality. Head rice yield percentages were improved by 21.08% with triple air flow reversal for 50cm bed depth and 17.53% with twice air flow reversal for 75cm bed depth compared to common drying practice. Moreover, air flow reversal drying technique remarkably improved drying capacity by 18% to 55% compared to conventional drying. This technique also had great potential to minimize the electrical energy usage by reducing 11%, 12% and 43% of energy required for drying 50cm, 75cm and 100cm rice bed depths respectively compared to existing industrial drying method in Malaysia. Findings also indicated that reducing the bed depth had dominant effects on head rice yield, rice whiteness degree and energy efficiency of drying operation. Finally, findings showed that when periodic air flow reversal was applied in two stage drying, the excellent milling quality of almost 70%, the highest throughput capacity of 0.037 ton m-2 h-1 and also the lowest specific electrical energy consumption of 91.93 kWh ton-1 were achieved. Therefore, air flow reversal technique combined with one and two stage drying can be strongly recommended to rice industries as applicable and effective options for improving rice milling quality and overcoming low efficiency of existing drying operations.